A CASE STUDY OF USING SONGS IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Dwi Ma’rifat (Journal of English and Education, 2017)
The research was an attempted to investigate the song-based activities and stages in teaching English vocabulary through song. Furthermore, it was intended to find out students’ responses towards the use of song in learning English vocabulary. This study was qualitative in nature and used a case study as its research design. Furthermore, this study employed three instruments in obtaining the data namely observation, interview and written documents. The participants of this study were twenty students of grade one in one private elementary school in Bandung. The results showed that there were four stages implemented by the teacher: opening, main, follow up and closing stage. In addition, the students showed positive response towards the used of song in learning English vocabulary. The students felt happy and enjoyed during the teaching learning process. Also, by using song, it aided them in understanding English vocabulary even better.